2018
DOI: 10.5152/tjg.2018.17660
|View full text |Cite
|
Sign up to set email alerts
|

Real world survival data of a rare malignancy: Anal cancer results in HIV negative patients from Turkey

Abstract: The short- and long-term prognoses of HIV-negative patients with anal squamous cell carcinoma were good, and low-grade toxicity was rare, thereby demonstrating that these patients can be successfully treated in a real-life setting with favorable outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Yuan et al [ 13 ] reported the differences in 5-year survival rates between node-negative and node-positive disease (76.7% versus 70.3%), and between stages I–II and stages III–IV (83.6% versus 71.2%), respectively. Esin et al [ 14 ] also reported an improvement in progression-free survival (PFS) with a lower T stage [ 14 ]. In addition, immunochemical staining of p16 also has prognostic value, with p16-positive tumours having a 2-year relapse-free rate of 78.2%, compared to 49.0% in p16-negative tumours, as reported by Wakeham et al [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yuan et al [ 13 ] reported the differences in 5-year survival rates between node-negative and node-positive disease (76.7% versus 70.3%), and between stages I–II and stages III–IV (83.6% versus 71.2%), respectively. Esin et al [ 14 ] also reported an improvement in progression-free survival (PFS) with a lower T stage [ 14 ]. In addition, immunochemical staining of p16 also has prognostic value, with p16-positive tumours having a 2-year relapse-free rate of 78.2%, compared to 49.0% in p16-negative tumours, as reported by Wakeham et al [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, more than two-thirds of the participants had complete radiological response following CRT, which is consistent with the responses seen in previous studies [ 16 20 ]. In a Turkish study evaluating HIV-negative patients, 100% response rate was demonstrated with the CRT approach in patients with ASCC, all of whom were CRs [ 14 ]. A similar study of 48 patients with ASCC was conducted by Day et al [ 21 ] in which CRs were documented in 79% of the patients via F-fluorodeoxyglucose positron emission tomography [ 21 ].…”
Section: Discussionmentioning
confidence: 99%